Divān-i Ḥasan Shauqī : dasvīn ṣadī hijrī meṉ Urdū shāʻirī kī rivāyat kā surāg̲ẖ - Shauqī, Ḥasan, active 16th century (Silsilah-yi mat̤būʻāt-i Anjuman Taraqqī-yi Urdū Pākistān, 1971)
Collected poetry (diwan) of a 16th century Urdu poet, hitherto, unpublished; includes an introduction by the editor (68 p.)